ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS DAN KESEJAHTERAAN PENGRAJIN TENUN IKAT DI KABUPATEN KLUNGKUNG - Swandewi, Ni Putu; Budhi, Made Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 4 (2024): Vol.13.No.4. APRIL 2024 [248-306]DO - 10.24843/EEP.2024.v13.i04.p02, 2024)
The study's objectives are as follows: To assess the direct influence of the number of working hours and work experience on the productivity of Ikat weavers in Klungkung district. To examine the direct impact of extended working hours, work experience, and productivity on the quality of life of Ikat weavers in Klungkung Province. To investigate how productivity acts as an intermediary factor in shaping the relationship between extended working hours and work experience on the well-being of Ikat weavers in Klungkung district. Regarding the study's population, it encompassed Ikat weavers from Klungkung province. The sample size for this research was determined using proportional random sampling. The data analysis technique employed was path analysis. The study's findings indicate that: Extended working hours and substantial work experience significantly and positively affect the productivity of Ikat weavers in Klungkung district. Increased working hours, accumulated work experience, and productivity have a significant and positive impact on the welfare of Ikat weavers in Klungkung district. Productivity serves as a mediating factor, influencing the relationship between extended working hours and work experience on the well-being of Ikat weavers in Klungkung District. keyword : welfare, productivity, hours worked, work experience.